The Role of Technology in Enhancing School Principals' Leadership Effectiveness: A Literature Reviews - Esisuarni, Esisuarni; Jasrial, Jasrial; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
This study aims to explore the role of technology in improving the effectiveness of school principals’ leadership by utilizing a literature reviews methodology. Relevant studies and sources were analyzed to examine how technology facilitates school management, data-driven decision-making, communication, and resource management. The findings reveal that digital-based management systems, analytics tools, and communication platforms help principals streamline administrative tasks, evaluate performance, and foster collaboration within the school community. Additionally, technology offers opportunities for professional development and strengthens engagement with stakeholders through social media and websites. However, challenges such as digital literacy gaps and data security concerns persist. Addressing these challenges is crucial for maximizing the potential of technology. The study concludes that the strategic and effective use of technology not only enhances school leadership but also contributes to creating better learning environments and improving educational quality. Continuous innovation and study are necessary to ensure technology remains a key driver in leadership effectiveness and satisfaction.